The Concept of Justice in The Murabahah Contract in The Perspective of Sharia Economic Law - Ratna Kulsum Lestari; Siti Saidatina (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The murabahah contract is one of the financing instruments in Islamic banking that is based on buying and selling with a profit margin that has been agreed between the bank and the customer. In its implementation, the concept of justice in the murabahah contract is often debated, especially related to transparency, balance of rights and obligations, and compliance with the principles of sharia economic law. This research aims to examine the concept of justice in murabahah contracts based on the perspective of sharia economic law. Using a qualitative method based on literature studies, this study examines various fiqh literature, DSN-MUI fatwas, and regulations related to Islamic banking in Indonesia. The results of the study show that fairness in murabahah contracts must be realized through the principle of information disclosure, the absence of gharar (ambiguity), and proportional risk sharing between banks and customers. In addition, the implementation of murabahah contracts that are not in accordance with the principles of justice, such as the determination of exploitative margins or lack of transparency in the disclosure of additional costs, can cause an imbalance in the legal relationship between the parties. Therefore, strict supervision and education to the public are needed regarding the rights and obligations in the murabahah contract so that the principle of justice in sharia economic law can be optimally enforced.